2011
DOI: 10.1007/s11368-011-0359-y
|View full text |Cite
|
Sign up to set email alerts
|

Compost application affects metal uptake in plants grown in urban garden soils and potential human health risk

Abstract: Purpose This study explores the effect of varying organic matter content on the potential human health risk of consuming vegetables grown in urban garden soils. Results and discussion Overall, the consumption of lettuce and green bean pods grown in some urban gardens posed a potential human health risk due to unacceptably high concentrations of cadmium or lead. In many cases, compost amendment increased the accumulation of metals in the vegetables. Even in soils considered uncontaminated by current guidelines,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 55 publications
2
45
1
8
Order By: Relevance
“…However, Murray et al (2011) pointed to possible health risks related to the use of compost. They found that compost amendment in some cases increased the accumulation of heavy metals in lettuce and carrots, and recommend guidelines for compost application.…”
Section: Recycling Managementmentioning
confidence: 99%
“…However, Murray et al (2011) pointed to possible health risks related to the use of compost. They found that compost amendment in some cases increased the accumulation of heavy metals in lettuce and carrots, and recommend guidelines for compost application.…”
Section: Recycling Managementmentioning
confidence: 99%
“…Consequently, the authors conclude that home gardening does not cause an increased risk (Sipter et al, 2008). Murray et al (2011) investigated the compost application effects on plant uptake with urban soils from Montreal and London and performed a risk assessment assuming that the vegetable consumption consisted of only beans, only lettuce, or only carrots. This resulted in HQs of up to 10.5 for Cd in lettuce in soils that are considered uncontaminated of Cd.…”
Section: Comparison To Risk Assessments Of Urban Gardening In Other Smentioning
confidence: 99%
“…However, it always depends on the type and quality of compost which then effect on metal solubility [3]. Besides, it has potential to discharge contaminants which originally exist in the compost which resulted leachate flows to the surface runoff or groundwater [4].…”
Section: Introductionmentioning
confidence: 99%